The Berkeley-Haas School of Business : codifying, embedding, and sustaining culture - Chatman, Jennifer; Lyons, Richard K. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2017)
The Berkeley-Haas School of Business case study outlines the history of Dean Rich Lyons' culture efforts. The case discusses the challenges the dean faced as well as future challenges to sustain the culture after the dean steps down at the end of the 2017/2018 school year.
Originally published in Chatman, J. A., & Lyons, R. K. (2017). The Berkeley-Haas School of Business: Codifying, embedding, and sustaining culture. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; Lyons, Richard K; Walter A. Haas School of Business (University of California, Berkeley); electronic books; Organizational change -- California